Pharmacoeconomic analysis of the genomic test Mammaprint® use for breast cancer patients treated at a private health institution in Brazil - Mansani, Fabio Postiglione; Koppen, Morgana (Mastology, 2020)
Breast cancer is the malignant neoplasia with the highest incidence in Brazilian women, below non-melanoma skin cancer1,2. About 75% of all breast cancers have a luminal biological profile (positive hormone receptors), based on the immunochemistry profile3. In addition to surgical management and hormonal treatment, some of these patients are selected to undergo chemotherapy, according to their clinical and pathological status. With the availability of some genomic tests, such as MammaPrint™, we can refine the indication of adjuvant chemotherapy, reducing financial costs associated with the use of medications and their complications, but mainly the cost of social treatment related to the significant toxicity of these therapies.